Changes in the EU and Global Milk and Dairy Products Market in View of Multilateral Trade Liberalisation - Pawlak, Karolina (Zeszyty Naukowe SGGW w Warszawie - Problemy Rolnictwa Światowego, 2014)
The aim of this article is to present the situation of the milk and dairy products market in the EU countries and in the countries which are the world’s major milk producers in view of changes caused by the potential liberalisation of the global milk trade. The volume of trade in milk and dairy products, as well as production, demand and prices paid by consumers were analysed. The study uses the general equilibrium model of the Global Trade Analysis Project (GTAP). Projections were made according to the propositions included in the modalities negotiated at the World Trade Organisation forum in December 2008. It was proved that the progressing liberalisation of foreign trade may increase the competitive pressure both on regional markets and on the global market. In consequence, the dairy producers and processors from the EU countries may lose part of the market to the suppliers from the countries with lower costs of production. Such countries as New Zealand, the USA, Brazil and China may benefit from the liberalization.